Approaches of Teaching Mathematics - Sarma, T.P. (SCHOOL SCIENCE, 2021)
Mathematics can be learnt and taught joyfully as the subject starts from day one as the child is born and raised at home. The different components of Mathematics like number, numbers operation, space, shape, measure, pattern and data handling can be taught through hands on activity and experiential learning. This paper highlights how the teaching can be made fun and joyful to the students from early days. This study explores the efficacy of the constructivist approach in primary mathematics education, specifically focusing on the teaching of concepts related to numbers, shapes and patterns. The research endeavors to observe the impact of this innovative pedagogical method on students’ learning and their overall engagement with the subject.